A Comparative analysis of Southern movement Crisis in Yemeni newspapers - Fatima Mohamed Al-Majdhoub; Azizah Hamzah; Mohd Yahya Mohamed Ariffin (University of Malaya, 2024)
The stand of the Yemeni government and its failure to address the consequences of the 1994 Yemeni civil war in the south parts for many years made strongly the fractions of the southern movement/ Al-Harak Al-Janubbiy to call for secession and to restore the former South of Yemen, and moved from peaceful means to the armed struggle. By using framing as the theoretical framework of this study, the content of Yemeni newspapers was analyzed as the research method. Four newspapers were selected, one official, two opposition, and one independent newspaper. The four papers represented different political orientations. Conflict made the most prominent frame across the four newspapers in reporting on the southern movement. The representation of the southern cause expressed the future of the Yemeni national unity by putting it in either frame changing the political system or getting back to zero point when each part may retain its former state.